BEHAVIOR OF RARE-EARTH METALS IN HYDROMETALLURGICAL PROCESSING OF PYROCHLOR-MONAZITE-GOETHITE ORES - N. A. Permyakova; E. I. Lysakova; S. I. Anufrieva; E. G. Likhnikevich (Тонкие химические технологии)
The article is dedicated to finding out the specific features of the behavior of rare-earth metals in hydrometallurgical processing of pyrochlore-monazite-goetite ores of the Chuktukonsky ore field is shown in the work. Chuktukonsky ore field is a potential source of rare earth metals. The mentioned ores are practically unenforceable. Hydrometallurgical methods for their complex processing were suggested. Agitational and autoclave nitric acid leaching depending on such technological parameters as temperature, HNO3 concentration, process duration, S:L ratio and the use of H2O2 were studied. The possibility of transferring manganese (that is present in a significant amount in the ore) into a nitric acid solution by hydrogen peroxide was considered. Based on the results of the conducted studies, the distribution of REM in the products of the hydrometallurgical conversion of pyrochlore-monazitegoetite ore was estimated. It was found out that incomplete opening of the ore material was observed during agitational leaching: average REM recovery into the solution is 60%. The study made it possible to solve the problem of purifying nitric acid solutions from phosphorus that hinders the subsequent extraction and separation of rare earth metal ions forming strong complexes with rare earths. Removal of phosphorus from the solution was achieved by conducting the process under pressure at elevated temperatures (200-230 0C). It was found that the optimal decomposition conditions ensuring the transfer of almost 99% of the REM into the nitric acid solution are: 25% solution of HNO3, ore size - 0.071 mm; 5% by volume H2O2; t(160 0С) = 1 h; t(230 0С) = 1 h, gradual temperature increase from 160 to 230 0С; S:L = 1:8. Autoclave nitric-acid leaching allows selecting rare earth metals from the main part of iron, phosphorus and niobium.